Peredaman Radikal DPPH oleh Ekstrak Metanol Spirulina platensis dan Teripang Emas (Stichopus hermanii) : DPPH radical scavenging by extract methanol of Spirulina platensis and gold sea cucumber (Stichopus hermanii) - mega safithri; Kustiariyah Tarman; Iriani Setyaningsih; Anisa Gianti Zhafira (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2020)
Spirulina platensis and Herrmann's sea cucumber (Sticophus hermanii) are marine biota that known have many health benefits. One of the benefit is as an antioxidant. The antioxidant activity of S.hermanii dan S. platensis from another country has been studied, but the antioxidant activity of both materials from Indonesia and the mixture haven’t studied yet. The purpose of this study was to test the antioxidant activity and to identify bioactive compounds of methanol extraxt of S. hermanii from Flores, S. platensis from Jepara and the mixture using DPPH method. Measurement of antioxidant activity used DPPH radical as an oxidant. Identification of bioactive compounds used a qualitative phytochemical test. The results showed that methanol extract of S.hermanii, S. platensis and the mixtures have IC50 value of 2,696.09±329.28 ppm, 324.92±4.06 ppm and 2,445.80±164.18 ppm. The methanol extract of Herrmann's sea cucumber contains alkaloids, saponins and triterpenoid, meanwhile S. platensis methanol extract contains alkaloids, flavonoids and steroids. Based on tests, the methanol extract from Herrmann's sea cucumber, S. platensis and the mixtures had very weak antioxidant activity with IC50 values more than 200 ppm.